Accessibility of Archival Reference Services - Nindya Indrasweri; Elya Riska Dwi Wahyuni; Rina Rakhmawati (Record and Library Journal, 2022)
Background of the study: Archival services are the final stage of records management, if they are based on an archive lifecycle approach. Accessibility aspects need to be studied in an effort to optimize archiving services so that archives can be widely used by the community. Purpose: This paper describes the process of archiving services and the accessibility aspects of archiving services carried out by Dinas Perpustakaan dan Kearsipan Kabupaten Sleman. Method: This research was a descriptive qualitative approach. Data was collected through observations, interviews, and literature studies. The data then has been analyzed in the following stages: observing the data, developing general sense, coding, compiling a narrative framework for presenting the results of data interpretation, and interpreting the data using data triangulation techniques. Findings: The accessibility aspect of archiving services at the Sleman Regency Library and Archives Service is viewed from four indicators, namely policies, facilities and infrastructure, service personnel, and archive user satisfaction. In policy indicators, the agency has been guided by legal products that are applied to technical archiving services, both at local and national levels. In terms of facilities and infrastructure indicators, in general, the department has met the minimum standard of availability and condition of archival service facilities and infrastructure. Conclusion: There are limitations in this study, namely the limitations of the analysis of each indicator which does not describe in depth so that archival services in the office are declared affordable. In addition, it is necessary to carry out a critical analysis of the results of the user satisfaction survey, namely through in-depth interview techniques to comprehensively understand the archive service process at the office.